CLASSIFICATION OF NATIONAL TYPES OF GAMES USED TO DEVELOP THE CREATIVE POTENTIAL OF PRESCHOOL CHILDREN - Нурбекова, Салтанат; Алимбекова, Анар; Қыяқбаева, Ұлбосын (Pedagogy and Psychology, 2022)
The article provides a classification of national games used to develop the creative potential of preschool children. The influence of national games on the development of cognitive processes, personality traits, which form the basis of the creative potential of children, was analyzed, and an analysis of national types of games was carried out. Taking into account the opinions of scientists who have studied national games, their features and rules are analyzed. National games develop memory, attention, creative imagination, creative thinking in preschoolers, hone their speech, broaden their horizons and encourage them to make extraordinary decisions. For example, "Counting Rhymes" develops the ability to count, teaches children numbers, explains the meaning of words in counting rhymes, poems are easy to remember and gives the child aesthetic education, reading them to the rhythm of music. Thanks to such opportunities, national games are of particular importance in the development of the creative potential of preschool children. The article focuses on the history of development, change and transformation of games, gives examples of national games that are often used in the pedagogical process.